An Operation Mode Selection Method of Dual-Side Bridge Converters for Efficiency Optimization in Inductive Power Transfer - Chen, Shuxin; Chen, Yang; Li, Hongchang; Dung, Nguyen Anh; Mai, Ruikun; Tang, Yi; Lai, Jih-Sheng (IEEE transactions on power electronics, 2020)
In inductive power transfer systems, impedance matching is critical in obtaining high efficiency. However, since the load impedance is subject to variations in most applications, especially wireless charging, maintaining impedance matching is a challenge. One valid solution is to maintain the equivalent load impedance at the optimal value against load variations by controlling a load-side power converter. Nonetheless, the system overall cost, size, and complexity can be increased. In this article, based on a proper selection between full-bridge and half-bridge modes of the inverter and rectifier, an operation mode selection method is proposed that can achieve semi-impedance-matching with large load variations. In general, with the proposed method, high overall efficiency can be obtained while neither additional power converters nor complicated control is required. A 1-kW prototype has been developed and the experimental results have verified the proposed method.